The Historical Background of the Slovak Press in the USA - Zahorska, Michaela Bakay; Kralova, Zdena; Cincebeaux, Helen Naine (Communications - Scientific letters of the University of Zilina, 2014)
It was the Slovak-American press that had unified the Slovak community in the USA. It had represented a relevant source of information about the Slovak community life as well as about the situation back home in Europe. The preservation of Slovak cultural heritage in a specific heterogeneous environment helped to awaken Slovak interest in national issues and encouraged the Slovak nation to speak up for their rights.